Automatization of Weight and Height Measurement Using Ultrasonic Sensors HC-SR04 and Load Cell Based on Arduino UNO at Integrated Services Posts (Posyandu) - Syifa Ulyanida; Amir Supriyanto; Sri Wahyu Suciyati; Junaidi Junaidi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
An automatic instrument for measuring weight and height has been realized using the HC-SR04 Ultrasonic Sensor and Arduino Uno-based load cell. This study aims to facilitate the weight and height measurement system to make data collection more efficient and accessible. The instrument is assembled by a frame made of PVC pipe to form a 112 cm high pole. The instrument's top is mounted with an Ultrasonic Sensor to detect height. At the bottom of the instrument, there are four load cells which are assembled with the principle of Wheatstone bridge and then connected to the HX711 module as a signal amplifier to the Arduino to detect weight. The measurement results are displayed on the LCD and the application interface created with Microsoft Visual Studio. The results showed that the instrument could measure and display the results of measuring weight and height well. The error value and accuracy of the Ultrasonic Sensor are 1.09% and 98.913%, respectively. The error values and load cell accuracy were obtained at 1.4% and 98.6%.